Sirolimus for Recurrent Giant Cell Myocarditis After Heart Transplantation: A Unique Therapeutic Strategy. (September 2019) - Patel, Apurva D.; Lowes, Brian; Chamsi-Pasha, Mohammed A.; Radio, Stanley J.; Hyden, Marshall; Zolty, Ronald
Abstract : Clinical Features: Giant cell myocarditis (GCM) is a rare and a rapidly progressive disorder with fatal outcomes such that patients often require heart transplantation. We present a case of recurrent GCM in a transplanted patient with a history of Crohn disease requiring a novel therapeutic approach. Therapeutic Challenge: After the orthotopic heart transplantation, GCM recurred on aggressive immunosuppression over the months, which included corticosteroids, basiliximab, tacrolimus, antithymocyte globulin, and rituximab. Although combination immunosuppressive therapy containing cyclosporine and 2–4 additional drugs including corticosteroids, azathioprine, mycophenolate mofetil, muromonab, gammaglobulin, or methotrexate have shown to prolong the transplant-free survival by keeping the disease under control, its role in preventing and treating recurrence posttransplantation is unclear. Solution: We added sirolimus, a macrolide antibiotic, with properties of T- and B-lymphocyte proliferation inhibition on the above immunosuppressive treatment postrecurrence of GCM. After sirolimus initiation and continuation, the patient has remained disease free.